Informed Choices: Gender Gaps in Career Advice - Yana Gallen; Melanie Wasserman (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper estimates gender differences in access to informal information regarding the labor market. We conduct a large-scale field experiment in which real college students seek information from 10,000 working professionals about various career paths, and we randomize whether a professional receives a message from a male or a female student. We focus the experimental design and analysis on two career attributes that prior research has shown to differentially affect the labor market choices of women: the extent to which a career accommodates work/life balance and has a competitive culture. When students ask broadly for information about a career, we find that female students receive substantially more information on work/life balance relative to male students. This gender difference persists when students disclose that they are concerned about work/life balance. In contrast, professionals mention workplace culture to male and female students at similar rates. After the study, female students are more dissuaded from their preferred career path than male students, and this difference is in part explained by professionals' greater emphasis on work/life balance when responding to female students. Finally, we elicit students' preferences for professionals and find that gender differences in information provision would remain if students contacted their most preferred professionals.
Keywords: C93; J16; J24; J71; 330; career information; gender; discrimination; correspondence study